Hydrological and Geological Analysis of Cohesive Soil and its Potential Risk in Middle Mountain Region: A Case Study of Naunuko Pahiro along Madi River, Kaski, Nepal - Baral, Prakash (Journal of Advanced Academic Research, 2022)
Middle Mountain region of Nepal is most often vulnerable in hydrological and geological aspect. Rainfall pattern, runoff, infiltration rate, different losses and soil parameters of cohesive soil (Silty clay) along with slope of slide (i) and depth of slide (H), factor of safety (F.O.S) along with probabilistic approach (correlation) are decisive factors pertaining to re-occurrence of landslide. Rainfall intensity, catchment area (A), runoff coefficient plays vital role in the estimation of flood frequency over a various period of time (25 years, 50 years and 100 years) respectively. The civil engineering structures along with middle mountain river are always vulnerable. Hence, its risk identification is prerequisite which is encompasses in the study. This study include hydrological and geological analysis of Taprang landslide (Naunuko Pahiro) which prevail at middle mountain region at an elevation ranging from 937m to 1047m of Kaski district, Gandaki  Provenance, Nepal. Soil test data, rainfall data, probability and statistical approach along with different empirical formulas are used to analyse hydrological and geological hazard. Factor of safety (F.O.S) is calculated on the basis of altering value of slope of slide (i) and depth of slide (H) from slope ranging 50° to 70°. With increase depth of slide greater than 10m, F.O.S. is less than one which is unstable. The slope stability found to be critical at depth of slide10m with 50° slopes.Higher ground water table, higher rate of run-off with an average rainfall 446.50cm and higher shear stress contribute to risk of landslide along with increase discharge at down- stream of landslide with possibility of flood hazard at Madi river bank.The result would give insight on nature of landslide and flood discharge which could support Madi Village Municipality, as well as other rural Municipality of middle mountain region of almost same elevation consisting of cohesive (Silty Clay) soil for shaping disaster risk reduction policies and strategies such that death and injuries as well as impact on civil engineering structures can be minimized.